Blended learning model based on portfolio and HOTS: How is it developed in LPTKs? - Herianto, Edy; Dahlan, Dahlan; Tripayana, I Nengah Agus; Basariah, Basariah; Setyowati, Rr. Nanik (Universitas Malikussaleh, 2022)
During the covid-19 pandemic, learning can no longer be done directly. LPTKs are given the option to organize blended learning, a mixture of offline and online. The main problem is how to develop blended learning, which includes portfolio focus and HOTS? This is development research. The aim is to find, develop and validate a product produced during 2020/2021, even the semester lecture process. The resulting learning products can be in the form of lecture handouts, final assignments, and lecture textbooks resulting from the application of portfolio-based and HOTS-based blended learning models. The process to be carried out in the development of learning products includes 1) planning (preliminary studies, proposal making), 2) product development, 3) product trials and revisions, and 4) dissemination and utilization. The results of the discussion on the acquisition of existing data can be concluded that the blended, portfolio, and HOTS-based learning activities have been carried out smoothly and comprehensively. The implementation of blended learning can be seen in the discussion of online and offline lectures and offline lecture exams. The student activity portfolio is contained in lecture activities, individual and group assignments, and individual exams. HOTS content is contained in assignments individually and in groups.